2014
DOI: 10.18632/oncotarget.2181
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils with protumor potential could efficiently suppress tumor growth after cytokine priming and in presence of normal NK cells

Abstract: In tumor-bearing state, the function of neutrophils is converted from tumor-suppressing to tumor-promoting. Here we report that priming with IFN-γ and TNF-α could convert the potential of neutrophils from tumor-promoting to tumor-suppressing. The neutrophils with protumor potential have not lost their responsiveness to IFN-γ and TNF-α. After priming with IFN-γ and TNF-α, the potential of the neutrophils to express Bv8 and Mmp9 genes was reduced. Conversely, the tumor-promotional neutrophils recovered the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 53 publications
0
26
0
1
Order By: Relevance
“…Human NK cells trigger neutrophil apoptosis through activating NK-cell receptor NKp46-and Fas-dependent pathways (47,48). The NK cell-produced cytokines, IFNg and TNFa, convert neutrophils from tumor promoting to tumor suppressing (49). TANs also influence tumor control by coordinating with other components of immune cells through their ability to suppress antitumor immunity (43,50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Human NK cells trigger neutrophil apoptosis through activating NK-cell receptor NKp46-and Fas-dependent pathways (47,48). The NK cell-produced cytokines, IFNg and TNFa, convert neutrophils from tumor promoting to tumor suppressing (49). TANs also influence tumor control by coordinating with other components of immune cells through their ability to suppress antitumor immunity (43,50,51).…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of IFN stimulation on neutrophil function were multifold: IFNs were found to suppress the pro-angiogenic activity of neutrophils [ 23 ], regulate neutrophil recruitment and life-span in the primary tumor [ 28 , 29 ] and suppress the metastasis promoting activity of neutrophils in the pre-metastatic niche [ 6 ]. Similarly, TNFα was shown to limit tumor growth independently as well as though activation of anti-tumor immunity in neutrophils [ 30 ].…”
Section: Neutrophil Development and Regulation Of Their Bone Marrow Rmentioning
confidence: 99%
“…TANs, the double-edged sword of innate immunity, are thus capable of being pro- or anti-tumorigenic depending on the tumor microenvironment [ 6 , 7 ]. Previous reports from our laboratory and others have shown that the inflammatory factors G-CSF/IL-6 [ 8 ] induce tumor-promoting neutrophils, while other mediators such as TNF-α and IFN-γ [ 9 ] or TGF-β blockade reverse the tumor-promoting effects of neutrophils [ 6 ], resulting in the recruitment and activation of TANs with an antitumor phenotype.…”
Section: Introductionmentioning
confidence: 99%